Pergulatan Perempuan Dusun Melawan Kemiskinan: Dari Eksploitasi Diri sampai Negosiasi: The Struggle of Rural Women Against Poverty: From Self-Exploitation to Negotiation - M. Khusna Amal (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2007)
Agricultural modernization in rural areas has failed to deliver just prosperity, instead perpetuating structural poverty for smallholder farmers, triggering massive urbanization, and seriously burdening women. This study aims to describe the struggle of women in Tenggiling Sawo Hamlet, Jember, to build a subject of power to confront family poverty. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal that women employ two main action patterns: self-exploitation through hard work, mobilizing all family resources, and utilizing the ethos of mutual cooperation; and negotiation, reflected in their economic roles that often exceed their husbands' income, their capacity as household heads, and their involvement in strategic domestic and public decision-making. In conclusion, a new awareness of equality has emerged, yet it has not sufficiently driven concrete social action to change subordinative gender relations. Therefore, strengthening women's collective capacity and implementing gender-responsive development policies are necessary. Modernisasi pertanian di pedesaan gagal membawa kemakmuran yang berkeadilan, justru melanggengkan kemiskinan struktural bagi petani kecil yang memicu urbanisasi massal dan membebani perempuan secara serius. Penelitian ini bertujuan mendeskripsikan perjuangan perempuan Dusun Tenggiling Sawo, Jember, dalam membangun subjek kekuasaan menghadapi kemiskinan keluarga. Melalui pendekatan kualitatif dengan studi kasus, data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa perempuan melakukan dua pola tindakan utama: eksploitasi diri melalui kerja keras, pengerahan seluruh sumber daya keluarga, dan pemanfaatan etos gotong royong, serta negosiasi yang tercermin dari peran ekonomi mereka yang sering melampaui pendapatan suami, kemampuan sebagai kepala rumah tangga, serta keterlibatan dalam pengambilan keputusan strategis domestik dan publik. Kesimpulannya, kesadaran baru tentang kesetaraan telah muncul, namun belum cukup mendorong aksi sosial konkret untuk mengubah struktur relasi gender yang subordinatif, sehingga diperlukan penguatan kapasitas kolektif perempuan dan kebijakan pembangunan yang berperspektif gender.